Exporting from a Small Landlocked Economy : An Assessment of Firm-Product-Destination Survival Rates in the Lao PDR - Stirbat, Liviu; Record, Richard; Nghardsaysone, Konesawang (2012)
This paper analyzes previously unreleased firm-level customs transaction data from the Lao PDR in order to assess the determinants of cohort survival among exporters. The authors find that export flows in value terms are dominated by the intensive margin, with large firms continuing to supply the same products to the same markets. On the extensive margin, new export spells for firms, products and firm-product-destination units are very small and short-lived, suggesting that although there is significant experimentation and discovery by firms, there is only limited capacity to stay in markets once an entry is made. Regression analyses of the factors that influence survival past the first year reveal that this is positively correlated with the initial dollar value (starting big makes a difference) and is helped by the firm's experience with the product and the destination, but hindered by a lack of focus. Agglomeration of exporters in the same destination with the same product is beneficial, an effect analogous to external economies of scale. The authors conclude by recommending that the focus of export promotion activity should be on helping existing exporters find and stay in new markets.